Exploring ethnomedicinal uses and relevance to phytochemical profile, pharmacological activities, and tissue culture of Tecoma stans (L.) Juss. ex Kunth - Rowida Omar; Marwa Elsbaey; Madiha Hassan; Mohamed Abd El-Salam (Phytomedicine Plus)
Ethnopharmacological relevance: Tecoma stans (L.) Juss. ex Kunth (Bignoniaceae) is a flowering plant native to the Americas and widely naturalized in tropical and subtropical regions. It has been traditionally used to treat diabetes, arthritis, and urinary disorders, with additional benefits including anti-inflammatory, antimicrobial, and antioxidant properties. Aim: Our review provides a comprehensive overview on the therapeutic potential of Tecoma stans focusing on its anti-diabetic properties, traditional ethnomedicinal uses, pharmacological activities, mechanisms of action of its key phytochemicals, and the comparison of these findings with results from plant tissue culture studies. Furthermore, the review explores the applications of Tecoma in green biotechnology and tissue culture, emphasizing conservation and sustainable production of bioactive compounds. Methodology: The literature on Tecoma stans was sourced from Google Scholar, PubMed, and ScienceDirect search engines, covering publications from the first report on the topic in 1954 until April 2024. The review focused on studies highlighting the ethnomedicinal uses, pharmacological activities, phytochemical composition, tissue culture, isolated endophytic fungi and relevant preclinical studies. Particular emphasis was placed on delineating the molecular mechanisms of action of isolated bioactive compounds and systematically evaluating the potential biotechnological applications of the plant, with a focus on sustainable production methodologies. Results: Several studies have demonstrated the efficacy of Tecoma stans in managing diabetes, with evidence suggesting that its therapeutic effectiveness is comparable to that of established conventional treatments. Key phytochemicals such as tecostanine, tecomine, anthranilic acid, and gallic acid have been linked to hypoglycemic, anti-inflammatory, antioxidant, and antimicrobial activities. Mechanistic insights suggest that these compounds modulate various biological targets involved in glycemic control and inflammation. While these compounds have shown promising activity against several biological targets, further clinical trials are necessary to fully validate these effects. Preclinical studies indicate low toxicity; however, comprehensive toxicity assessments are still needed to confirm safety for clinical use. Additionally, tissue culture approaches and isolated endophytes have been investigated as sustainable methods for the production of these bioactive secondary metabolites. Conclusions: In summary, the phytochemicals derived from Tecoma stans exhibit significant therapeutic potential, particularly in the management of diabetes and related conditions, without notable side effects. These findings suggest that Tecoma stans could be considered a viable alternative to conventional treatments for diabetes and other ailments. Furthermore, advancements in green biotechnology, plant tissue culture techniques and endophytes isolation and identification offer promising avenues for large-scale production and conservation, warranting further exploration and potential integration into clinical practice.